Evaluation of the immune response of peripheral blood mononuclear cells cultured on Ti6Al4V-ELI polished or etched surfaces - Abreu, Hugo; Lallukka, Mari; Raineri, Davide; Leigheb, Massimiliano; Ronga, Mario; Cappellano, Giuseppe; Spriano, Silvia; Chiocchetti, Annalisa (Frontiers in Bioengineering and Biotechnology, 2024)
While titanium and its alloys exhibit excellent biocompatibility and corrosion resistance, their polished surfaces can hinder fast and effective osseointegration and other biological processes, such as angiogenesis, due to their inert and hydrophobic properties. Despite being commonly used for orthopedic implants, research focuses on developing surface treatments to improve osseointegration, promoting cell adhesion and proliferation, as well as increasing protein adsorption capacity. This study explores a chemical treatment intended for titanium-based implants that enhances tissue integration without compromising the mechanical properties of the Ti6Al4V substrate. This treatment creates a complex surface topography with micro-and nano-texture and modifies the chemistry of the surface oxide layer. The acid etched surface contains an abundance of hydroxyl groups, crucial for promoting bone growth and apatite precipitation, while also enabling further functionalization with biomolecules. However, recognizing that inflammation contributes to nearly half of early implant failures, we assessed the impact of this treatment on the immune response, particularly on cell viability, cytokine production, and T-cell phenotype. While cell viability remained high in both groups, untreated discs triggered an increase in Th2 cells and a decrease of the Th17 subset. Furthermore, peripheral blood mononuclear cells exposed to untreated discs displayed a rise in various pro-inflammatory and antiinflammatory cytokines compared to the control and treated groups. Conversely, the treated discs showed a similar profile to the control, suggesting the treatment's potential to mitigate inflammation by enhancing biocompatibility.